Analisis Neraca Air Permukaan DAS Ciliman - Isvan Taufik (Jurnal Ilmu Lingkungan, 2019)
Water balance is an estimate of the availability and needs of water in a watershed area. The water balance is very important considering the human need for water resources is a major requirement. The purpose of this study includes; (1) Analyzing the distribution of the influence of rainfall observation stations in each of the Ciliman sub-watersheds, (2) Analyzing the mainstay discharge in each Ciliman sub-watershed, and (3) Analyzing the potential availability of raw water in the Ciliman watershed. The types of data used in this study are secondary data including: (1) monthly rainfall data from 4 rainfall observation stations included in the Ciliman watershed, (2) climatological data from BMKG Taktakan Serang Station in 1998-2015, (3) Map of Watershed Ciliman and (4) Population data. Data analysis methods used include; regional rainfall analysis, analysis of water availability (evapotranspiration analysis, Mock model analysis), and analysis of water requirements. The results of the analysis showed that the highest rainfall occurred in January, and the lowest rainfall occurred in August. Overall, the water available in the Ciliman watershed is sufficient with the peak occurring at the beginning and end of the year. Water availability is estimated based on surface water discharge, where peak discharge occurs in January and minimum discharge occurs in August. The water balance in general in the Ciliman watershed is quite high with the highest water debit of 61.75 m3/s occurring in March and the lowest (minimum) discharge around 5.26 m3/s in August. The total water requirement for the Ciliman watershed area is 38.86 m3/s, consisti of; Water demand for irrigation is the highest water requirement reaching 37.96 m3 s with a total irrigated area reaching 5,423 hectares. Domestic water needs are 0.48 m3/s with a total population of 314,524 people served. Water requirements for industry are 0.000040 m3/s or relatively relatively small. While the water demand for the Tanjung Lesung Special Economic Zone is 0.42442 m3/s.